الاحتراق النفسي لدى العاملين مع بعض فئات ذوي الاحتياجات الخاصة في ضوء متغيري الخبرة المهنية والفئة المتعامل معها - خرف الله، علي; العايب، جهيدة سعد; بلعالية، محمد Belaliah, Mohammed (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاجتماعية والانسانية, 2019)
This paper aimed to identify the difference in the levels of psychological burnout among workers with some special needs groups in the light of some variables (professional experience and the customer class). The following questions were asked: Are there any statistically significant differences in the degree of psychological burnout among workers with some groups of people with disabilities special to the variable professional experience? Are there any statistically significant differences in the level of psychological burnout among workers with special needs groups according to the customer class? A descriptive comparative approach was applied and a 31-item questionnaire was applied to a sample that was selected in a non-deterministic and intentional manner consisting of 48 workers in some of El-Oued centers. The first hypothesis was not realized, while the second hypothesis was realized.
هدفت الدراسة إلى التعرف على الاختلاف في مستويات الاحتراق النفسي لدى العاملين مع بعض فئات ذوي الاحتياجات الخاصة في ضوء بعض المتغيرات (الخبرة المهنية والفئة المتعامل معها) اعتمادا على التساؤلين التاليين هل توجد فروق ذات دلالة إحصائية في درجة الاحتراق النفسي لدى العاملين مع بعض فئات ذوي الاحتياجات الخاصة تعزى إلى متغير الخبرة المهنية؟ وهل توجد فروق ذات دلالة إحصائية في مستوى الاحتراق النفسي لدى العاملين مع بعض فئات ذوي الاحتياجات الخاصة حسب الفئة المتعامل معها؟ وللإجابة عليها تم إتباع المنهج الوصفي المقارن، وبتطبيق استبيان مكون من 31 بند على عينة تم اختيارها بأسلوب لا احتمالي وبطريقة قصدية والمكونة من 48 عاملاً في بعض مراكز مدينة الوادي، حيث تم التوصل إلى أن الفرضية الأولى غير محققة، بينما الفرضية الثانية محققة.
Keywords: الاحتراق النفسي -- ذوي الاحتياجات الخاصة -- الخبرة المهنية